2017
DOI: 10.1097/md.0000000000006443
|View full text |Cite
|
Sign up to set email alerts
|

The influence of different growth hormone addition protocols to poor ovarian responders on clinical outcomes in controlled ovary stimulation cycles

Abstract: Background:Growth hormone (GH) is used as an adjuvant therapy in in vitro fertilization and embryo transfer (IVF-ET) for poor ovarian responders, but findings for its effects on outcomes of IVF have been conflicting. The aim of the study was to compare IVF-ET outcomes among women with poor ovarian responders, and find which subgroup can benefit from the GH addition.Methods:We searched the databases, using the terms “growth hormone,” “GH,” “IVF,” “in vitro fertilization.” Randomized controlled trials (RCT) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
73
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 32 publications
9
73
0
1
Order By: Relevance
“…No significant differences in endometrial thickness were observed. These results agree with the conclusions of previous meta‐analyses reporting that GH treatment increased pregnancy and the live birth rate and providing new effective methods of longer term GH administration from the early stage of follicle recruitment before COH.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…No significant differences in endometrial thickness were observed. These results agree with the conclusions of previous meta‐analyses reporting that GH treatment increased pregnancy and the live birth rate and providing new effective methods of longer term GH administration from the early stage of follicle recruitment before COH.…”
Section: Discussionsupporting
confidence: 91%
“…GH has been applied as an adjuvant option in the field of in vitro fertilization (IVF) treatment since the 1990s, but there is still controversy regarding its efficacy in improving the IVF cycle outcome . A retrospective, matched case–control study reported that the administration of GH during the luteal phase before a microdose gonadotropin‐releasing hormone (GnRH) agonist flare protocol for IVF did not improve the outcomes of patients with poor ovarian responder (POR), whereas a recent meta‐analysis showed that the addition of GH could significantly improve the clinical pregnancy rate and live birth rate . Although there is no consensus on GH administration in terms of patient criteria, ovarian stimulation protocol, GH treatment duration or optimized dosage, there is a trend to prolong GH treatment prior to ovarian stimulation instead of concurrent exposure to Gonadotropin .…”
Section: Introductionmentioning
confidence: 99%
“…Our study findings revealed that co-treatment with GH in PORs could improve the rate of clinical pregnancy and the number of collected oocytes (metaphase II), fertilized oocytes, and transferred embryos; however, we did not find the effect of this treatment on chemical pregnancy and the number of live births. A recent systematic review and meta-analysis by Li et al, (2017) demonstrated that co-treatment with GH in controlled ovarian stimulation cycles could improve clinical pregnancy rate, live birth rate, the number of collected oocytes, and the number of MII oocytes, but they reported no significant difference between experimental and control groups in terms of implantation and fertilization rates. In total, adding GH on a routine regimen for ovary stimulation can increase the likelihood of clinical pregnancy and also can mature fertilized oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent systematic review (17) that has been conducted in 2017 including 11 articles and 663 women, it was reported that GH addition significantly increased clinical pregnancy rate (RR 1.65, 95% CI 1.23 -2.22; p<0.001), live birth rate (RR 1.73, 95% CI 1.25 -2.40; p<0.001) and number of oocytes retrieved (SMD 1.09, 95% CI 0.54 -1.64; p<0.001) . (17)The subgroup analysis indicated that clinical pregnancy and live birth rates were significantly increased when GH was co-treated with gonadotropin, however, there were no significant differences found as for the clinical pregnancy rate and live birth rate when it was supplemented during the preceding luteal phase of the cycle (17).…”
Section: Growth Hormone (Gh) Supplementationmentioning
confidence: 98%